Investigation of Heavy Metal Removal by a Submerged Aquatic Plant (Myriophyllum spicatum) in a Batch System - Keskinkan, O. (Asian Journal of Chemistry, 2016)
The experimental results regarding the performance of a laboratory scale wetland in removing heavy metals (Zn2+, C2+, Cd2+) were presented. A total of ten glass aquaria were used to constitute the wetland. River sand was placed at the beds of the aquaria to keep the plants in an upright position. After establishing the experimental conditions, five aquaria were planted with Myriophyllum spicatum and the other five control aquaria were left unplanted. Heavy metals were used at 1, 2, 4, 8 and 16 mg/L concentrations. Operating took two weeks. Removal of metals occurred in 1–5 d. Removal rates ranged from 87.3–99.9% for Zn, 90–98.5% for Cu and 58.9–90.3% for Cd. The results show that the M. spicatum system, which was able to remove Zn2+, Cu2+ and Cd2+ has a good removal capacity.